The Management Of Pioneering Inclusion Class At MI Karang Kemiri Banyumas Central Java - Roikhatul Janah (Al-Bidayah : jurnal pendidikan dasar Islam, 2019)
Inclusive education is a service system in the world of education and teaching that combines students who have limitations with normal students in a regular class to get common knowledge from a teacher. Data shows that Banyumas District has more than 2000 students with special needs, Madrasah Ibtidaiyah (MI) 1, Karang Kemiri is a pilot MI to implement inclusive classes in Banyumas Regency. This study aims to find out how the inclusion class management strategies in the MI 1 Pakuncen Banyumas pioneering inclusion class. This research is a qualitative approach, with the focus of research on the inclusive class management strategies in the pioneering inclusion class of MI Karang Kemiri, Pakuncan, Banyumas. Inclusion class management strategies in MI 1 Karang Kemiri include the management of educators and the management of students.